Political and Cultural Boundaries in South China Sea Disputes between China and Indonesia - Lutfi, Khoirur Rizal (Faculty of Law Universitas Lampung, 2023)
China's assertion of sovereignty over the South China Sea through its nine-dash line, encompassing areas traditionally utilized for fishing, has precipitated territorial disputes with neighboring countries. Indonesia, for instance, refers to the overlapping zone as part of the North Natuna Sea, grounding its claim on the 1982 United Nations Convention on the Law of the Sea (UNCLOS). This divergence in territorial claims has notably strained relations between China and Indonesia. This paper presents the stance of international law on establishing political and cultural boundaries as the foundation for territorial claims to propose a dispute resolution framework for the South China Sea conflict that seeks a win-win outcome for all parties involved. The findings of the analysis indicate that political and cultural boundaries can be legitimized under international law. Political boundaries are reinforced by a state's ability to convert agreements into international treaties through bilateral, regional, or global mechanisms. On the other hand, cultural boundaries necessitate a thorough compilation of evidence to support China's historical claims, a process that a recognized decision-making body must adjudicate. Notwithstanding, the efficacy of any legal adjudication may be undermined without a comprehensive cultural reconciliation effort. Crucially, the resolution of the South China Sea dispute hinges on the adherence of states to international agreements, the rulings of dispute resolution bodies, and the implementation of settlement measures that incorporate a cultural dimension.